DIVORCE IMPOSED AND THE CHARTER OF FUNDAMENTAL RIGHTS OF THE EU - Monica Di Monte (European Scientific Journal, ESJ, 2014)
The Court of Italian Cassation with the ordinance of June 6 th 2013, n. 14323 put again to the Italian Constitutional Court the decision on the case of a couple of consorts whose transsexual husband had gotten the rectification of attribution of sex. The controversial joint concernes the fate of the marriage tie following the change of sex of one the consorts. Besides the annotation on the action of birth of the variation of the registry data there was the annotation related automatic cessation of marriage. The Court of Italian Cassation admits that a form is created of “imposed divorce”. To the light of this it is legitimate the doubt the vompatibilities with the normative constitutional and with the contained prescriptions in the CEDU, in which he affirms the right of selfdetermination in the relative choices personal and sexual ball’identita of every individual. The Court of Italian constitution, also recognizing importance to the homosexual unions, it exclusively interprets the marriage among heterosexual.